О грамматическом своеобразии текстов русских эпиграмм - Tatiana Wołyniec (Studia Rossica Posnaniensia)
In the article some peculiarities of grammatical realization of Russian epigram texts (mainly nominal architecture of speech, demand for elliptical and comparative patterns, evaluation characterizing predicates, updating of secondary functions of grammatical forms) will be discussed.